The development of an ontology model for early identification of children with specific learning disabilities - Rosmayati Mohemad; Nur Fadila Akma Mamat; Noor Maizura Mohamad Noor; Arifah Che Alhadi (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Ontology-based knowledge representation is explored in special education environment as not much attention has been given to the area of specific learning disabilities such as dyslexia, dysgraphia and dyscalculia. Therefore, this paper aims to capture the knowledge in special education domain, represent the knowledge using ontology-based approach and make it efficient for early identification of children who might have specific learning disabilities. In this paper, the step-by-step development process of the ontology is presented by following the five phases of ontological engineering approach, which consists of specification, conceptualization, formalization, implementation, and maintenance. The details of the ontological model’s content and structure is built and the applicability of the ontology for early identification and recommendation is demonstrated.